2018
DOI: 10.1111/tpj.13824
|View full text |Cite
|
Sign up to set email alerts
|

Lack of ACTPK1, an STY kinase, enhances ammonium uptake and use, and promotes growth of rice seedlings under sufficient external ammonium

Abstract: Ammonium influx into plant roots via the high-affinity transport system (HATS) is down-modulated under elevated external ammonium, preventing ammonium toxicity. In ammonium-fed Arabidopsis, ammonium transporter 1 (AMT1) trimers responsible for HATS activity are allosterically inactivated in a dose-dependent manner via phosphorylation of the conserved threonine at the carboxyl-tail by the calcineurin B-like protein 1-calcineurin B-like protein-interacting protein kinase 23 complex and other yet unidentified pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 59 publications
(112 reference statements)
0
31
0
Order By: Relevance
“…10B . ACTPK1 (Os02g0120100) has been demonstrated to phosphorylate and inactivate the ammonium transporter AMT1;2 in rice seedling roots under sufficient ammonium conditions 31 . The Os02g0807000 gene encodes phosphoenolpyruvate carboxylase kinase 1 (PPCK1) that plays an important role in the regulation of phosphoenolpyruvate carboxylase (PEPC) and plant metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10B . ACTPK1 (Os02g0120100) has been demonstrated to phosphorylate and inactivate the ammonium transporter AMT1;2 in rice seedling roots under sufficient ammonium conditions 31 . The Os02g0807000 gene encodes phosphoenolpyruvate carboxylase kinase 1 (PPCK1) that plays an important role in the regulation of phosphoenolpyruvate carboxylase (PEPC) and plant metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The Arabidopsis NIGT1 homolog is involved in the integration of nitrate and phosphate signals at the root tip 30 . More recently, the Os02g0120100 gene encoding ACT domain-containing protein kinase 1 (ACTPK1), a homolog of Arabidopsis serine/threonine/tyrosine kinase 46 (STY46), was identified by transcriptome analysis of ammonium-responsive genes in rice roots 31 . Further genetic and biochemical studies demonstrated that ACTPK1 can phosphorylate and inactivate AMT1;2, a major ammonium transporter, under ammonium-sufficient conditions 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Members of the STY kinase family are dual-specificity kinases that possess catalytic Ser/Thr and Tyr domains, and they regulate some plant metabolic and developmental processes through phosphorylation of target proteins [24,25]. For example, STY protein kinases appear to have important roles in ammonium transport in rice seedling roots [26], in storage oil accumulation in Arabidopsis siliques [27], and in stress response and seed development in cucumber and peanuts [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Hsieh et al [60] found that the N-regulated genes, Os02g0120100, Os02g0807000 and Os06g0692600 etc., which encode transcription factors, protein kinases and protein phosphatases and may be involved in the regulation of early −N responses in rice roots. The serine/threonine/tyrosine (STY) protein kinase, ACTPK1, enhances ammonium uptake and use, and promotes growth of rice seedlings under sufficient ammonium [61] . A calcium-dependent protein kinase gene, esl4, which may function upstream of nitrogen-metabolism genes [62] .…”
Section: Discussionmentioning
confidence: 99%